دراسة واقعية نموذج تسعير الأصول الرأسمالية في بورصة الجزائر "سهم أن س ي أ رويبة كنموذج" - بدروني, عيسى; شريط, حسين الأمين (Université de M'sila, 2017)
Several studies have confirmed the reality of this relationship in various stock exchanges around the world. However, field studies often produce divergent results between a supporter and a critic of its reality. However, despite these contradictions, no explicit results have been found that completely negate the reality of the model. This paper will relate to the study of the reality of the model on the Algiers Stock Exchange. Where the proceeds of any financial asset are assumed to be linearly linked to the proceeds of the risk-free asset and market returns through the beta risk factors.
Keywords: capital asset pricing model, Algiers stock Exchange- ALEX, beta coefficient, risk returns.